Enzymatic inhibitory activity of iridoid glycosides from Picrorrhiza kurroa against matrix metalloproteinases: Correlating in vitro targeted screening and docking. (February 2019) - Rathee, Dharmender; Lather, Viney; Grewal, Ajmer Singh; Dureja, Harish
Graphical abstract: Highlights: In vitro studies were performed to check the enzyme inhibitory potential of iridoid glycosides against MMPs (-2 and -9). In silico analysis was done to evaluate the interactions of iridoid glycosides against MMP-2 and -9 enzymes. Results revealed a direct interaction of compounds with active site residues to inhibit MMP-9 activities. Investigation showed that the iridoid glycosides are worthy to consider suitable therapeutic agents against MMPs activity. Abstract: One specific group of MMPs; gelatinases A (MMP-2) and B (MMP-9) are of precise interest in view of the development and progression of cancer. In the current work, an attempt was made to investigate the enzymatic inhibitory activity of Kutkin (KT), Kutkoside (KS), and Picroside I (PS) by inhibition assay and to further check the downregulation of the expression of mRNA levels of MMP-2 and -9. Further in silico docking studies were performed to investigate the interaction of KT, KS and PS with MMP-2 and MMP-9. The results revealed a dose dependent cytotoxic activity of the compounds under investigation and showed a significant inhibition of MMP-9 in comparison to the activity against MMP-2. In addition, a considerable decrease in expression of mRNA levels (MMP-9) was observed in KT, KS, and PS-treated MDA-MB-231 and MDA-MB-435 cancer cells as was detected by reverse transcriptase polymerase chain reaction (semi-quantitative RT-PCR). The molecular docking studies between KT, KS, PS with MMPs revealed that KT, KS, PS occupied the active site of MMP-9 and showed better binding interactions in comparison to MMP-2. The binding energies of the complexes were –7.4, –7.1 and –7.2 kJ/mol for KT, KS and PS with MMP-9, respectively and –8.9, –8.0 and –8.0 kJ/mol for KT, KS and PS with MMP-2, respectively. The findings from the in vitro studies revealed that KT, KS and PS exhibited significant anti-proliferative effects on both MDA-MB-231 and MDA-MB-435 breast cancer cells. In addition, the results of inhibition assay showed that MMP-9 activity was significantly inhibited by KT, KS and PS and the results were consistent with in silico assay.